2019
DOI: 10.1111/cpr.12564
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of long non‐coding RNA TNRC6C‐AS1 protects against thyroid carcinoma through DNA demethylation of STK4 via the Hippo signalling pathway

Abstract: Objectives: Thyroid carcinoma (TC) represents a malignant neoplasm affecting the thyroid. Current treatment strategies include the removal of part of the thyroid; however, this approach is associated with a significant risk of developing hypothyroidism.In order to adequately understand the expression profiles of TNRC6C-AS1 and STK4and their potential functions in TC, an investigation into their involvement with Hippo signalling pathway and the mechanism by which they influence TC apoptosis and autophagy were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…For instance, YAP (or YAP1), a major transducer in downstream of Hippo pathway, is amplified and nuclear accumulated in a variety of cancers 19 . LncRNA TNRC6C antisense RNA 1 (TNRC6C‐AS1) was reported to be abundantly expressed in thyroid carcinoma and could regulate the subcellular localization and activation of YAP, leading to the promotion of cell proliferation and tumorigenicity 20 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, YAP (or YAP1), a major transducer in downstream of Hippo pathway, is amplified and nuclear accumulated in a variety of cancers 19 . LncRNA TNRC6C antisense RNA 1 (TNRC6C‐AS1) was reported to be abundantly expressed in thyroid carcinoma and could regulate the subcellular localization and activation of YAP, leading to the promotion of cell proliferation and tumorigenicity 20 …”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, MIR22HG was shown through bioinformatics analysis to be associated with the Hippo signaling pathway in thyroid cancer. Yang et al 69 demonstrated that overexpression of the lncRNA TNRC6C-AS1 promotes the proliferation of thyroid cancer cells while inhibiting their autophagy and apoptosis. A further investigation conducted by Peng et al 55 indicated that TNRC6C-AS1 is localized in the nucleus and that its overexpression significantly promotes the methylation of cytosine-phosphate-guanine (CpG) islands in the STK4 promoter region via the recruitment of methyltransferases, thus downregulating the expression of STK4.…”
Section: Lncrnas Regulate the Hippo Pathway In Cancersmentioning
confidence: 99%
“…It is one of the antisense RNA of the STK4 gene. STK4 protein was reported to regulate many types of cancers, including liver cancer [34], prostate cancer [35], and thyroid carcinoma [36]. However, the effect of its antisense RNA was still unclear.…”
Section: Introductionmentioning
confidence: 99%